Academic autonomous learning in two Ecuadorian universities: a statistical and student-centered perspective - Núñez-Naranjo, Aracelly F. (2025)
This study explores the role and extent of academic autonomous learning among students from two public universities in central Ecuador. Recognizing the importance of self-directed learning in higher education, especially in post-pandemic contexts, the research aims to assess how students apply autonomous work strategies in their academic routines. A total of 158 students from four different academic programs participated in the study. Data were collected using the validated CETA instrument, which evaluates six dimensions of autonomous work: expansion, collaboration, conceptualization, planning, exam preparation, and participation. The research adopts a quantitative, non-experimental, cross-sectional approach. Statistical methods included descriptive analysis, Pearson correlations, t-tests, ANOVA, and Chi-square tests. The findings reveal a high level of internal consistency in the CETA dimensions and strong correlations between key strategies, particularly between expansion and exam preparation. While no statistically significant differences were found between genders or institutions, some programs displayed subtle variations. The study concludes that autonomous academic work is a critical factor in students’ academic performance and professional development. It highlights the importance of fostering self-regulation, planning, and motivation in the educational process. These findings provide valuable insights for higher education institutions seeking to strengthen autonomy-oriented teaching strategies.